POSTCOLONIALISM IN ORHAN PHAMUIC'S SNOW : A LITERARY ANALYSIS - Siyaswati, Siyaswati (WAHANA, 2012)
The purpose of this paper is to reveal the postcolonialism approach a literary study in Novel Snow by Orhan Phamuk. Post colonialism is inspired by Orientalism and produced due to social injustice in colonized countries. "Snow" is a novel which takes place in the border city of Kars and explores the conflict between Islamism, Westernism, poverty and headscarf ban in modem Turkey. It also explored vast trajectories of history, art, culture, the persistence of memory and tradition in their everyday lives and the poignancy and beauty of the human experience.